Cognitive impairment and risks of osteoporosis: A systematic review and meta-analysis. (March 2023) - Zhao, Yangyang; Chen, Heqing; Qiu, Fei; He, Jianquan; Chen, Jian
Highlights: This study provides the latest evidence on the correlation between osteoporosis and cognitive impairment. we used strict inclusion criteria to obtain a homogenous sample so that we could reduce bias because of unclear definitions as much as possible. This study expands the understanding of osteoporosis and cognitive impairment. Abstract: Objective: To systematically assess the association between osteoporosis and cognitive impairment, and to provide new light on the prevention of cognitive impairment in patients with osteoporosis. Method: A comprehensive research of Embase, Cochrane Library, PubMed, Web of Science, CNKI, Wangfang Data and VIP was performed from inception to January 2022, using the search term 'osteoporosis' and 'cognitive impairment'. Literature screening, data extraction and quality evaluation were conducted by two reviewers independently, and meta-analysis was performed by RevMan 5.4 software. Results: A total of 8 studies (136222 participants) were included. Meta-analysis showed that patients with osteoporosis had an increased risk of cognitive impairment [ OR =2.01, 95% CI (1.63–2.48), P< 0.01]. This initial meta-analysis had significant heterogeneity, and subgroup analysis suggested that potential heterogeneity in different study types, age and outcome indicators. Conclusion: Patients with osteoporosis are at increased risk of cognitive impairment, and osteoporosis intervention could prevent or delay the onset of cognitive impairment for those at risk.